Bloodstream Infections Leading to Sepsis: Clinical and Microbiological Profiling of Bacteremia among Hospitalized Patients in Surabaya, Indonesia - Marwasyifa, Nuritsna; Asmarawati, Tri Pudy; Setiawan, Firman; Endraswari, Pepy Dwi (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: Bacteremia poses a significant health risk due to its frequently atypical presentation and potential progression to sepsis. Understanding its clinical profiles and causative pathogens is essential for timely diagnosis and effective management. This study examined the characteristics of bacteremia cases in 2022 at Universitas Airlangga Hospital, Surabaya, Indonesia. Methods: A retrospective, descriptive observational study was conducted utilizing hospitalized bacteremia patients' medical records. A total of 107 patients met the inclusion criteria, which required positive blood cultures along with complete data on age (≥19 years), sex, comorbidities, clinical manifestations, bacterial infection diagnosis, outcomes, and pathogen characteristics. Medical records failing to meet these criteria were excluded. The data were categorized and analyzed by variables. Results: Bacteremia predominantly affected patients aged >65 years (36.4%), males (50.5%), and those with diabetes (54.2%) and with pneumonia (79.4%). Key symptoms included tachycardia (55.1%), tachypnea (55.1%), anemia (65.4%), and leukocytosis (71.0%), despite normal vitals observed in numerous cases. Gram-positive bacteria were most prevalent (69.7%), mainly Staphylococcus hominis (18.7%). Escherichia coli (9.3%) was the leading Gram-negative isolate, while extended-spectrum beta-lactamase (ESBL) strains (4.2%) were the primary multidrug-resistant organisms (MDRO). Sepsis and septic shock were equally prevalent (35.5%). Mortality (64.5%) occurred primarily due to septic shock (49.3%). Conclusion: Sepsis and septic shock frequently occur in older males with diabetes and pneumonia. Key symptoms include frequent tachycardia, tachypnea, anemia, and leukocytosis. Septic shock, the leading cause of death in bacteremia patients, frequently occurs alongside infections by Staphylococcus hominis and ESBL-producing Escherichia coli.   Highlights: 1. This study offers fresh perspectives on the clinical profiles of hospitalized bacteremia patients and the characteristics of causative bacteria at Universitas Airlangga Hospital, a topic that has been minimally explored in the Indonesian medical community. 2. It highlights the prevalence of bacteremia, its clinical manifestations, and outcomes to determine the mortality rate of hospitalized bacteremia patients. 3. This study provides valuable data that can help inform future infection control strategies to manage and prevent bloodstream infections, hence enhancing healthcare outcomes by emphasizing the importance of improving clinical data collection and monitoring.